N1-P2 event-related potentials and perceived intensity are associated: The effects of a weak pre-stimulus and attentional load on processing of a subsequent intense stimulus - Favero, J.D.; Luck, Camilla; Lipp, Ottmar; Nguyen, A.T.; Marinovic, Welber (2023)
A weak stimulus presented immediately before a more intense one reduces both the N1-P2 cortical response and the perceived intensity of the intense stimulus. The former effect is referred to as cortical prepulse inhibition (PPI), the latter as prepulse inhibition of perceived stimulus intensity (PPIPSI). Both phenomena are used to study sensory gating in clinical and non-clinical populations, however little is known about their relationship. Here, we investigated 1) the possibility that cortical PPI and PPIPSI are associated, and 2) how they are affected by attentional load. Participants were tasked with comparing the intensity of an electric pulse presented alone versus one preceded 200 ms by a weaker electric prepulse (Experiment 1), or an acoustic pulse presented alone with one preceded 170 ms by a weaker acoustic prepulse (Experiment 2). A counting task (easy vs. hard) manipulating attentional load was included in Experiment 2. In both experiments, we observed a relationship between N1-P2 amplitude and perceived intensity, where greater cortical PPI was associated with a higher probability of perceiving the ‘pulse with prepulse’ as less intense. Moreover, higher attentional load decreased observations of PPIPSI but had no effect on N1-P2 amplitude. Based on the findings we propose that PPIPSI partially relies on the allocation of attentional resources towards monitoring cortical channels that process stimulus intensity characteristics such as the N1-P2 complex.